Women in the defense of human rights in Mexico - Chávez León, Katia; Vilchis Cordero, Gretha Jimena (Revista Internacional & Comparada de Derechos Humanos, 2023)
This article seeks to make visible the role of women human rights defenders in society and the complexity of the context in which they carry out their work. In this sense, from a gender perspective, the double risk condition suffered by women defenders is analyzed; first, the multiple forms of gender-based discrimination that exist in Mexican society; and second, the endemic violence that they systematically reproduce oppression against them. This document proposes the design of protection policies for women defenders that consider the gender characteristics or reasons that differentially and disproportionately affect women, as a minimum response that the State must consider in the environment of violence.
Keywords: Women defenders; gender perspective; violence against women human rights defenders; protection of women human rights defenders